9(3x+9)-5=

Simple and best practice solution for 9(3x+9)-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3x+9)-5= equation:


Simplifying
9(3x + 9) + -5 = 0

Reorder the terms:
9(9 + 3x) + -5 = 0
(9 * 9 + 3x * 9) + -5 = 0
(81 + 27x) + -5 = 0

Reorder the terms:
81 + -5 + 27x = 0

Combine like terms: 81 + -5 = 76
76 + 27x = 0

Solving
76 + 27x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-76' to each side of the equation.
76 + -76 + 27x = 0 + -76

Combine like terms: 76 + -76 = 0
0 + 27x = 0 + -76
27x = 0 + -76

Combine like terms: 0 + -76 = -76
27x = -76

Divide each side by '27'.
x = -2.814814815

Simplifying
x = -2.814814815

See similar equations:

| 7/3x-1=2x | | y=5/2x-1(5,3) | | 15.27=.965*x-.548 | | 2/1-3x-3=-4 | | 6X-4Yndy=4x+2 | | 7x^2-24x+104=0 | | 12y-3[y+5]=48 | | 3(4x+12)+7x-15= | | 2sin^2x+5sinx=1 | | (xy^2+y^2+x^2)dx-x^2dy=0 | | (3x-2y)(3x-2y)(2x+5Y)= | | 8(5x+6)+6x= | | (xy^2+y^22+x^2)dx-x^2dy=0 | | -84+3x=-6x+69 | | 3x+.3125=.75-.125x-.5 | | x^2+y^2+2x-14y+25=0 | | 5[m-3]+2m=27 | | 6.50(10)+2x=4(x+10) | | 10(a-6)=-25 | | 6(2x+5)+12= | | -3x-7-5=5x-2(2x+2) | | 2(7x+1)+11x= | | Graphx+3y=300 | | 0=x^4-36 | | (2x-11)+11= | | y=x^4-36 | | -60+5x=-4x+66 | | 5(x+7)-2x=3(2x+5)-1 | | 3xy-y+3x=1008 | | e^3x-4=7 | | 1.5=.75 | | 4p+8-3p=33 |

Equations solver categories